Nitrogen Fertilization of Fodder Sorghum M. P. Chari ( Sorghum Bicolor) Grown Under Rainfed Condition - Abhichandani, C T; Gill, A S; Maurya, R K; Mannikar, N D (Annals of Arid Zone, 2016)
Trials with fodder sorghum cultivar M. P. Chari conducted under rainfed conditions at the Indian Grassland and Fodder Research Institute, Jhansi showed that (I) Nitrogen application both basal and split, increased green fodder, dry matter and crude protein yields over no nitrogen and significant yield increases were obtained up to 90 kg N/ha. (2) Split application of nitrogen gave no added advantage over basal application. (3) Crude protein content (percentage of dry matter) of shoot tended to be very much higher during low rainfall year of 1970 than during the almost normal rainfall year of 1969.